Konstruksi Islam Rahmah Li Al-‘Alamin K.H. Ahmad Hasyim Muzadi - Ibnul Arobi (Institut Ilmu Keislaman Zainul Hasan Genggong, 2018)
The problems raised in this paper are; how Islamic idea rahmah li al-'alamin K.H. Ahmad Hasyim Muzadi; and this paper reveals that the Islamic idea of rahmah li al-'alamin is a term that is contained in the Qur'an. This idea emerges as a form of reaction or response, in order to wean the lara that is engulfing the Islamic community, especially stigmatization addressed to Islam, as a religion contained in the teachings of seeds that can foster a Muslim to commit acts of violence. As a manifestation of the universalization of Islam, in the context of Indonesia, Islam rahmah li al-'alamin takes its form as presented by Walisongo, the pattern of Islam which is propagated by means of peace-building and wisdom to the existence of local culture (Indonesia). Keywords: Islam rahmah li al-'alamin and K.H. Ahmad Hasyim Muzadi.